1989
DOI: 10.1080/03079458908418619
|View full text |Cite
|
Sign up to set email alerts
|

Economic effects of subclinical infectious bursal disease on broiler production

Abstract: A survey of the infectious bursal disease (IBD) status of 85 clinically normal broiler flocks was carried out. Flocks were grouped into three categories: flocks without IBD lesions (category A), flocks with typical acute IBD lesions (B) and flocks with typical chronic IBD lesions (C). Category A flocks achieved a net income per 1,000 birds which was 11% better (P<0.05) than category B flocks and 14% better (P<0.01) than category C flocks. The 85 broiler houses used by the surveyed flocks during production were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In addition, the plant condemnation rate due to septicaemia-toxaemia syndrome may be increased tenfold from 0.5% to over 5% in affected flocks. McIlroy et al (1989) documented 14% depression in financial return from broiler flocks with subclinical IBD compared with unaffected flocks surveyed in…”
Section: Economic Significance Of Ibdmentioning
confidence: 99%
“…In addition, the plant condemnation rate due to septicaemia-toxaemia syndrome may be increased tenfold from 0.5% to over 5% in affected flocks. McIlroy et al (1989) documented 14% depression in financial return from broiler flocks with subclinical IBD compared with unaffected flocks surveyed in…”
Section: Economic Significance Of Ibdmentioning
confidence: 99%
“…The virus replicates in the bursa of Fabricius and other lymphoid tissues resulting in immunosuppression, which leads to an increased susceptibility to other infectious agents and a lack of humoral response to vaccinations (Allan, Faragher, & Cullen, ; Faragher, Allan, & Wyeth, ; Rosenberger & Gelb, ). IBDV infections are widespread and have a severe economic impact on the commercial poultry production (McIlroy, Goodall, & McCracken, ; Zachar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…. IBDV infections are widespread and have a severe economic impact on the commercial poultry production (McIlroy, Goodall, & McCracken, 1989;Zachar et al, 2016).…”
mentioning
confidence: 99%
“…• McIlroy et al (1993) found that there was a positive impact of increasing vitamin E in the diets of birds with subclinical IBD. Their analysis showed that the performance of flocks with subclinical IBD was consistently worse in terms of net income, feed conversion ratio and average weight per bird than flocks without subclinical disease (McIlroy et al, 1989). In their trial the average net income of flocks with subclinical IBD and fed a high vitamin E-containing diet was 10% better than that from flocks with subclinical IBD and fed a normal vitamin E-containing diet.…”
Section: Infectious Bursal Diseasementioning
confidence: 97%